Peran Guru Bimbingan Konseling terhadap Prestasi Belajar Siswa Kelas XI SMA Mazra’atul Ulum Paciran Lamongan Tahun Pelajaran 2017-2018 - Syaifudin Zuhri; Sutopo Sutopo (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2021)
Guidance and counseling teachers or we can call them BK teachers are very essential positions in educational institutions. Because they are needed by students for all the problems they face in following the lesson. Learning achievement is a process of effort made by a person to obtain a new change in behavior as a whole, as a result of his own experience in interaction with his environment. The changes are relatively constant and scar. In this regard, the learning process and change are evidence of the processed results. Learning is not only learning the subject, but also the arrangement, habits, perceptions, pleasures or interests, social adjustment, various other skills and aspirations. Thus, a person is said to be learning if there is a change in himself due to training and experience through interaction with his environment and maximum achievement. The design in this study is a naturalistic qualitative research that aims to determine the role of BK teachers on student achievement. The findings in this study have a large influence on the existence of a BK teacher on the progress of student achievement in Class XI SMA Mazra'atul Ulum Paciran, both from student discipline and learning achievement. By looking at the explanation and explanation above, because the researcher uses naturalistic qualitative methods that explain the results of research naturally according to the objects that occur in the field, From the results of the research above, it is recommended for future researchers to develop the potential and existing resources, to determine the part of the research. other variables, to improve student achievement in high school institutions.